Project: USMCares - ’USM Creative Arts Embrace Sustainability’ - Anderson Ee, Hasnul J. Saidon, Noor Azlina Mohamed Khalid, Lattalilat Group UNIMAS; U-WARISains-seni USM (Wacana Seni Journal of Arts Discourse, 2011)
Showcasing six different projects related to the idea of sustainability, especially the environment.